EFEK NEUROPROTEKTIF EKSTRAK DAUN GINKGO BILOBA PADA NEUROPATI PERIFER : Scoping Review - Della Intan Rachmawati Lamas (2021)
Peripheral neuropathy is a peripheral nerve disorder with multiple causes, can affect sensory, motor, autonomic, or mixed nerves, and can be acute or chronic. Peripheral neuropathy is also a neurological disease that practitioners commonly encounter. The administration of medicinal plants such as Ginkgo biloba as an adjuvant therapy to treat peripheral neuropathy is still a consideration until now. Ginkgo biloba leaf extract's effect is to inhibit axonal degradation and inhibit the production of proinflammatory cytokines such as TNF-α. This study aims to see clinical evidence of Ginkgo biloba leaf extract's neuroprotective effect on peripheral neuropathy by the scooping review method and journal searches carried out until January 2, 2021. The investigation was carried out in the published literature centre with the keywords "Ginkgo biloba" OR "Ginkgolides" OR "Egb 761 "AND" Neuroprotective "OR" Peripheral Neuropathy ". A total of six studies were selected that met the inclusion and exclusion criteria. This study proves that there is one clinical evidence regarding Ginkgo biloba leaf extract's neuroprotective effect on peripheral neuropathy in humans. Five research articles prove that there is a clinical improvement in peripheral neuropathy after being given Ginkgo biloba leaf extract in mice. All of selected review show clinical improvement in peripheral neuropathy after being given Ginkgo biloba leaf extract.